2017
DOI: 10.1097/igc.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Recurrence After Fertility-Preserving Surgery in Patients With Borderline Ovarian Tumors: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Unilateral cystectomy (19.4%) and serous BOTs (19.2%) are significantly associated with higher recurrence rates, and no negative impact of laparoscopy on recurrence can be demonstrated when compared with laparotomy in the meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Nevertheless, when we particularly examined whether the surgical type was cystectomy or not (Model B), cystectomy increased the risk of recurrence. This finding is consistent with results from a multi‐center study, systematic reviews and meta‐analysis which showed that cystectomy was a significant risk factor for BOT recurrence …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, when we particularly examined whether the surgical type was cystectomy or not (Model B), cystectomy increased the risk of recurrence. This finding is consistent with results from a multi‐center study, systematic reviews and meta‐analysis which showed that cystectomy was a significant risk factor for BOT recurrence …”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with results from a multi-center study, systematic reviews and meta-analysis which showed that cystectomy was a significant risk factor for BOT recurrence. [23][24][25] In the univariate analyses, peritoneal implants and chemotherapy were associated with BOT recurrence. These variables were included in initial multivariate models.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a large proportion of patients who underwent FSS experienced invasive recurrence [13]. Regarding surgical patterns, a meta-analysis showed that unilateral cystectomy is significantly associated with high recurrence rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…Microinvasion was defined as stromal invasion restricted to an area of no more than 10 mm 2 [9]. Several surgical options are mentioned in this study such as FSS, which was performed to conserve the uterus and at least one ovary, and radical resection, which included hysterectomy and bilateral salpingo-oophorectomy [10]. Moreover, the concepts of surgery types need to be clarified: staging, and non-staging surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Microinvasion was defined as stromal invasion restricted to an area of no more than 10 mm 2 [9]. Several surgical operation types are mentioned in this study, such as FSS, which was performed to conserve the uterus and at least a portion of one ovary [10], and radical resection, which included total hysterectomy and bilateral salpingo-oophorectomy. Moreover, the concepts of three surgery types need to be clarified: complete staging, incomplete staging, and unstaged surgeries.…”
Section: Methodsmentioning
confidence: 99%